Improving the Ability of Listening to the Content of Folk Stories through Audio Visual Media in Class VI Students of Elementary School in Selatan Minahasa District - Wulan Mercy Wulur; Mayske Rinny Liando; Viktory Nicodemus Joufree Rotty (Researchparks Publishing, 2022)
The purpose of this research is to improve students' listening skills on the content of folklore for elementary schools in South Minahasa Regency. The learning process in the classroom must be supported by existing media so that teachers can improve students' abilities in the learning process. The media used in this research is audio-visual to improve students' ability to listen to the contents of folklore. Furthermore, the method used is Classroom Action Research (CAR) which focuses on improving the process and learning outcomes towards a better direction. Before conducting the research, the researchers conducted a survey on December 8, 2021 in the sixth grade of SD Inpres Pakuure with the folklore of Toar and Lumimuut. The results of the pre-cycle researchers get the result that is 17%, the KKM determined by the school is 75. This means that the sixth grade students of SD Inpres Pakuure have not achieved the expected results. Researchers conducted Cycle I with the hope of increasing the results of students' grades in class, the scores already obtained in Cycle I increased by 25% to 42%. However, the results obtained by students cannot be said to be complete so that the researcher continues this research to Cycle II to get significant results. The results of the research in Cycle II, researchers have obtained very maximum results, even exceeding the Minimum Completeness Criteria. Cycle II increased by 50% from Cycle I to 92%. This study has obtained appropriate results. Researchers have discontinued the research because they have obtained the expected results.